2020
DOI: 10.1093/jn/nxaa148
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Nicotinamide Dose-Dependently Regulates Body Phosphorus Excretion via Altering Type II Sodium-Phosphate Co-Transporter Expressions in Laying Hens

Abstract: Background Dietary supplemental nicotinamide is used to treat hyperphosphatemia in humans. However, the mechanisms of its impact on body phosphorus homeostasis remain unclear. Objective This study was to determine effects and molecular mechanisms of 3 dietary nicotinamide concentrations on body phosphorus homeostasis in laying hens. Methods Hy-Line Brown laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Phosphate binders inhibited the absorption of phosphate, but also up-regulated the active phosphate transporter Npt-2b in the intestine (Isakova et al, 2015). Nicotinamide, the metabolite of vitamin B3, could reduce phosphate by inhibiting the intestinal phosphate transporter Npt-2b, which is a secondline drug for phosphate lowering treatment (Ren et al, 2020). It has been reported that nicotinamide can reduce phosphate by 12-34% in end-stage CKD dialysis patients (Vogt et al, 2019).…”
Section: Other Approachesmentioning
confidence: 99%
“…Phosphate binders inhibited the absorption of phosphate, but also up-regulated the active phosphate transporter Npt-2b in the intestine (Isakova et al, 2015). Nicotinamide, the metabolite of vitamin B3, could reduce phosphate by inhibiting the intestinal phosphate transporter Npt-2b, which is a secondline drug for phosphate lowering treatment (Ren et al, 2020). It has been reported that nicotinamide can reduce phosphate by 12-34% in end-stage CKD dialysis patients (Vogt et al, 2019).…”
Section: Other Approachesmentioning
confidence: 99%
“…Our results showed that dietary vitamin D 3 deficiency reduces the mRNA expression of FGFR (including FGFR1 , FGFR2 , FGFR3 and FGFR4 ) and VDR in the calvaria, but has no effect on the liver. Hepatic FGF23 mRNA expression is not sensitive to dietary phosphorus, nicotinamide and vitamin D 3 levels ( Ren et al., 2020b , 2020c ), suggesting that FGF23 may be related to other physiological functions in laying hens. Calvaria FGFR1 can sense changes in extracellular phosphorus levels and regulate the production of FGF23 ( Takashi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, eggshell thickness was measured using a dial pipe gauge (ETG-1061; Robotmation, Co., Ltd., Tokyo, Japan); eggshell strength was measured using a texture analyzer (EFG-0503; Robotmation, Co., Ltd., Tokyo, Japan); egg yolk color, albumen height, and Haugh units were tested using a multifunction egg quality analyzer (EMT-5200; Robotmation, Co., Ltd., Tokyo, Japan); specific gravity was measured using a flotation method in saline solutions; shell index was calculated as shell weight of whole egg; 2) 24-h total excreta from each laying hen was collected for the determination of phosphorus and calcium excretion; 3) calvaria, liver, intestinal mucosa (duodenum, jejunum and ileum) and kidney samples were collected after euthanasia, frozen in liquid nitrogen, and then transferred to a −80 °C freezer until further analysis. All experimental analysis methods were performed as previously described ( Liu et al., 2018 ; Ren et al., 2020b , 2020c ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, dietary phytase inclusion enhanced serum P concentration ( Table 5 ), which might have stimulated FGF23 secretion from the bone ( Ren et al., 2017 ). A higher serum FGF23 circulation has been shown to be coupled with a greater NaPi-IIb protein expression in the duodenal mucosa of layers ( Ren et al., 2020 ). Taken together, expression of P transporters is consistent with intestinal P absorption in broilers.…”
Section: Discussionmentioning
confidence: 99%